Cigarette smoking significantly alters sperm DNA methylation patterns. (26th September 2017) - Jenkins, T. G.; James, E. R.; Alonso, D. F.; Hoidal, J. R.; Murphy, P. J.; Hotaling, J. M.; Cairns, B. R.; Carrell, D. T.; Aston, K. I.
Summary: Numerous health consequences of tobacco smoke exposure have been characterized, and the effects of smoking on traditional measures of male fertility are well described. However, a growing body of data indicates that pre‐conception paternal smoking also confers increased risk for a number of morbidities on offspring. The mechanism for this increased risk has not been elucidated, but it is likely mediated, at least in part, through epigenetic modifications transmitted through spermatozoa. In this study, we investigated the impact of cigarette smoke exposure on sperm DNA methylation patterns in 78 men who smoke and 78 never‐smokers using the Infinium Human Methylation 450 beadchip. We investigated two models of DNA methylation alterations: (i) consistently altered methylation at specific CpGs or within specific genomic regions and (ii) stochastic DNA methylation alterations manifest as increased variability in genome‐wide methylation patterns in men who smoke. We identified 141 significantly differentially methylated CpGs associated with smoking. In addition, we identified a trend toward increased variance in methylation patterns genome‐wide in sperm DNA from men who smoke compared with never‐smokers. These findings of widespread DNA methylation alterations are consistent with the broad range of offspring heath disparities associated with pre‐conception paternal smoke exposure and warrant further investigation to identify the specific mechanism by which sperm DNA methylation perturbation confers risk to offspring health and whether these changes can be transmitted to offspring and transgenerationally.